THE INFLUENCE OF CULTURE, SOCIAL, PERSONAL AND PSYCHOLOGY ON BUYING DECISION (Case Study at Consumen Ciplaz Mall Lampung in Bandar Lampung) - hanif, ahmad aliffia (Jurnal Kompetitif Bisnis, 2021)
This research was aimed to find out the effect of culture, social, personal and psychology on buying decision and on customer CiplazMall Lampung. This approach of research was explanatory. The population in this study were customer of Ciplaz Mall Lampung. The sampling technique in this study is accidental sampling with a sample of 100 respondents. The data were obtained from questionnaire through likert scale. Based on the results of the research and data analysis, culture has a positive and significant effect on the buying decision, social has a positive and significant effect on the variable of buying decision, personal has a positive and significant effect on the variable of buying decision, psychology has a positive and significant effect on the variable of buying decision. Based on simultaneous result, it proves that culture, social, personal and psychology have significant influence toward buying decision. This suggest that the effect of culture, social, personal and psychology on buying desion customer satisfaction can increase buying decision Ciplaz Mall Lampung.